Human Rights and Law Enforcement at Sea Arrest, Detention and Transfer of Piracy Suspects - Petrig, Anna (Brill, 2014)
Law enforcement at sea has become an increasingly important tool for combating transnational crime. Such law enforcement operations are commonly directed by multinational missions composed of military rather than police forces, and are often carried out in maritime areas not subject to national jurisdiction. Because of these characteristics, maritime law enforcement operations touch upon many unresolved human rights issues. In the present study, counter-piracy operations off the coast of Somalia and in the Indian Ocean serve as the quintessential example of how law enforcement measures taken at sea may fall short of international human rights standards. An unprecedented number of national and multinational missions have been deployed to counter the phenomenon of piracy off the coast of Somalia and in the region. Their mandate includes the arrest, detention and transfer for prosecution of piracy suspects. The book at hand examines the procedures pertinent to the decision whether to release piracy suspects, prosecute them in the seizing State or transfer them to a third State, and the detention regime pending such decisions. The study provides a critical analysis of the compatibility of these procedures with international law, first and foremost human rights law. Using piracy as an example, it demonstrates that the characteristics of national and multinational law enforcement at sea may lead to a deviation from certain human rights standards - standards that the States in question readily accept and apply in their land-based, territorial law enforcement operations. At the centre of the analysis are two unique case studies, which provide insight into the arrest, detention and transfer procedures in both a multinational context and a purely interstate setting. This work is a valuable contribution to legal scholarship dealing with the human rights dimension of maritime law enforcement operations. It is a useful, timely and innovative resource for both academics and legal practitioners alike, or any person interested in the applicability and scope of human rights norms in the maritime context.